PERAN KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN KETERLIBATAN KERJA TERHADAP KOMITMEN ORGANISASI PADA CV SUMBER REJEKI SLEMAN - Amini Zaidah (JURNAL ILMIAH EDUNOMIKA, 2021)
The research aims to determine the role of transformational leadership, organizational culture and work involvement on organizational commitment at CV Sumber Rejeki Sleman. By using hypothesis testing multiple linear regression analysis techniques, t-test and f-test. The entire population the number of employees is 48 people. Research data collections using a questionnaire. The results showed first, transformational leadership has on effect on organizational commitment with a significance value of 0,815 > 0,05 and tcount value of 0,236 < 2,015. Second, organizational culture has a positive effect on organizational commitment with a significance value 0,009 < 0,05 and tcount value of 2,742 > 2,015. Third, job involvement has no effect on organizational commitment with a significance value of 0,433 > 0,05 and tcount value of -0,791 < 2,015. Keywords : Transformational leaderhip, Organizational Culture, Job Involvement and Organizational Commitment.